Getting Started with Terraform - Second Edition - Shirinkin, Kirill (Packt Publishing Limited, 2017)
bBuild, Manage and Improve your infrastructure effortlessly./bh2About This Book/h2ulliAn up-to-date and comprehensive resource on Terraform that lets you quickly and efficiently launch your infrastructure/liliLearn how to implement your infrastructure as code and make secure, effective changes to your infrastructure/liliLearn to build multi-cloud fault-tolerant systems and simplify the management and orchestration of even the largest scale and most complex cloud infrastructures/li/ulh2Who This Book Is For/h2This book is for developers and operators who already have some exposure to working with infrastructure but want to improve their workflow and introduce infrastructure as a code practice. Knowledge of essential Amazon Web Services components (EC2, VPC, IAM) would help contextualize the examples provided.